The Role of Growth-Oriented Challenge Acceptance in Enhancing Organizational Performance of State-Owned Banks in Central Java (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Organizational performance in state-owned banks increasingly depends on employees’ ability to adapt to dynamic work environments and accept challenging tasks proactively. Traditional development approaches often overlook this critical mechanism. This study develops a conceptual model of Growth-Oriented Challenge Acceptance (GOCA) as a mediating mechanism linking Adhocracy Culture and Goal Commitment to Organizational Performance. Data were collected through an online questionnaire from employees of four state-owned banks in Central Java (BNI, Mandiri, BRI, and BTN) and analyzed using SEM-AMOS. The results show that Adhocracy Culture and Goal Commitment significantly influence GOCA. Furthermore, Adhocracy Culture, Goal Commitment, and GOCA significantly affect organizational performance, with GOCA having the strongest impact. GOCA also mediates the effects of Adhocracy Culture and Goal Commitment on performance. The model explains 57.2% of the variance in GOCA and 87.9% of the variance in organizational performance. This study extends Goal Setting Theory and provides practical insights for performance enhancement
Keywords: Growth-Oriented Challenge Acceptance; Adhocracy Culture; Goal Commitment; Organizational Performance; State-Owned Banks